Efficacy and Benefit of Postoperative Chemotherapy in Micropapillray or Solid Predominant Pattern in Stage IB Lung Adenocarcinoma: A Systematic Review and Meta-Analysis - Xu, Congcong; Zhu, Kanghao; Chen, Dong; Ruan, Yuhang; Jin, Zixian; Qiu, Hongbin; Chen, Baofu; Shen, Jianfei (Frontiers in Surgery, 2021)
Background: The benefit of postoperative chemotherapy remains controversial for patients with either a micropapillary or solid pattern in stage IB non-small cell lung cancer. This study is designed to explore the significance of postoperative chemotherapy in patients with either a micropapillary or solid pattern in stage IB lung adenocarcinoma. Method: To conduct the meta-analysis, PubMed, Cochrane Library, Embase and Medline were used to collect literature on long-term follow-up studies published before March, 2021, involving postoperative chemotherapy for patients with either a micropapillary or solid pattern in stage IB lung adenocarcinoma as compared to non-postoperative chemotherapy. Survival data was extracted from the literature, including the overall survival and disease-free survival. Based on overall survival and disease-free survival, hazard ratios and their 95% of confidence intervals were applied to assess the prognostic effect of postoperative chemotherapy. Review Manager software was used to merge the effect size for the meta-analysis. Result: In total, 6 papers with 956 patients were included. In terms of the prognosis of patients suffering from lung cancer when receiving postoperative chemotherapy, this study comprehensively reviews and evaluates the available evidence of micropapillary or solid patterns. After excluding the heterogeneity between the studies, we found that the pooled results from 6 studies report that postoperative chemotherapy was associated with a better overall survival rate when compared with non-postoperative chemotherapy (hazard ratio=0.58, 95% confidence interval, 0.44-0.77; P = 0.0002). Postoperative chemotherapy also significantly improved the disease-free survival in patients with both a micropapillary or a solid pattern in stage IB lung adenocarcinoma (postoperative chemotherapy versus non-postoperative chemotherapy, hazard ratio=0.51, 95% confidence interval, 0.40-0.64; P < 0.001). However, a subgroup analysis showed that compared with non-postoperative chemotherapy, tumor size was unrelated to the prognosis of patients in stage IB undergoing postoperative chemotherapy (hazard ratio= 0.98, 95% confidence interval, 0.94-1.02; P = 0.27). Conclusion: Postoperative chemotherapy results in a better long-term survival rate for patients with either a solid or a micropapillary pattern in stage IB lung adenocarcinoma. Multi-center, prospective, clinical trials are needed to validate our findings.